How do dinosaurs choose their pets? - Yolen, Jane (Blue Sky Press, an imprint of Scholastic Inc., 2017)
At first, the dinosaurs try to bring home all manner of wild beasts, but in the end, they learn to bring home an appropriate animal from a shelter or pet store and to love and care for it with attention.